PENGARUH DUKUNGAN KELUARGA, KUALITAS PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR AGAMA HINDU ANAK RETARDASI MENTAL DI SLB D YPAC BALI - Ayu Putu Dewi Ary Sukanti (Guna Widya: Jurnal Pendidikan Hindu, 2021)
Family support on learning achievement of Hinduism through the regression line equation = 50.393 + 0.376 X1 with a contribution of 50.8% and an effective contribution of 19.0%, (2) there is an effect of learning quality on learning achievement of Hinduism through the regression line equation: = 55.578 + 0.314 X2 with a contribution of 52.2% and a contribution of 19.3%, (3) there is an influence of learning motivation on the learning achievement of Hindu teachers through regression line equations = 55.549 + 0.318 X3 with a contribution of 71.9% and effective contribution of 41.7%, and (4) there is a joint influence between family support, learning quality, and learning motivation on learning achievement of Hindu teachers through regression line equations = 45.676 + 0.141 X1 + 0.116 X2 + 0.185 X3 contribution with amounted to 41.7%. Based on these findings, it can be ignored that there is a positive and significant influence between family support, learning quality, and learning motivation on learning achievement of Hinduism for children with mental retardation in SLB D YPAC Bali separately or simultaneously.